Scavenging mitochondrial hydrogen peroxide by peroxiredoxin 3 overexpression attenuates contractile dysfunction and muscle atrophy in a murine model of accelerated sarcopenia. Issue 3 (24th February 2022) - Ahn, Bumsoo; Ranjit, Rojina; Kneis, Parker; Xu, Hongyang; Piekarz, Katarzyna M.; Freeman, Willard M.; Kinter, Michael; Richardson, Arlan; Ran, Qitao; Brooks, Susan V.; Van Remmen, Holly
Abstract: Age‐related muscle atrophy and weakness, or sarcopenia, are significant contributors to compromised health and quality of life in the elderly. While the mechanisms driving this pathology are not fully defined, reactive oxygen species, neuromuscular junction (NMJ) disruption, and loss of innervation are important risk factors. The goal of this study is to determine the impact of mitochondrial hydrogen peroxide on neurogenic atrophy and contractile dysfunction. Mice with muscle‐specific overexpression of the mitochondrial H2 O2  scavenger peroxiredoxin3 (mPRDX3) were crossed to Sod1KO mice, an established mouse model of sarcopenia, to determine whether reduced mitochondrial H2 O2 can prevent or delay the redox‐dependent sarcopenia. Basal rates of H2 O2  generation were elevated in isolated muscle mitochondria from Sod1KO, but normalized by mPRDX3 overexpression. The mPRDX3 overexpression prevented the declines in maximum mitochondrial oxygen consumption rate and calcium retention capacity in Sod1KO. Muscle atrophy in Sod1KO was mitigated by ~20% by mPRDX3 overexpression, which was associated with an increase in myofiber cross‐sectional area. With direct muscle stimulation, maximum isometric specific force was reduced by ~20% in Sod1KO mice, and mPRDX3 overexpression preserved specific force at wild‐type levels. The force deficit with nerve stimulation was exacerbated in Sod1KO compared to direct muscle stimulation, suggesting NMJ disruption in Sod1KO. Notably, this defect was not resolved by overexpression of mPRDX3. Our findings demonstrate that muscle‐specific PRDX3 overexpression reduces mitochondrial H2 O2  generation, improves mitochondrial function, and mitigates loss of muscle quantity and quality, despite persisting NMJ impairment in a murine model of redox‐dependent sarcopenia. Abstract : Compared to innervating wildtype muscle (Top), redox‐dependent sarcopenia is accompanied by increased neuromuscular junction disruption and hydrogen peroxide from the mitochondria (Middle). Scavenging mitochondrial hydrogen peroxide protects the muscle from contractile dysfunction and atrophy independent of NMJ disruption in a mouse model of redox dependent sarcopenia (Bottom).